Fenomena Politik Uang (Money Politic) Pada Pemilihan Calon Anggota Legislatif di Desa Sandik Kecamatan Batu Layar Kabupaten Lombok Barat - Lina Ulfa Fitriani; L Wiresapta Karyadi; Dwi Setiawan Chaniago (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2019)
This research aims to determine the political phenomenon of money that occurs in the community, it is difficult to stop and become the habit or tradition of certain political candidates or contestants to the community ahead of Of the elections to get the most support and vote from the community. The purpose of research is to know the factors of the cause of money politics, how the process of occurrence in the community and the impact of the political practice of money for the community. The research uses a paradigm analysis of social behaviour with Exchange theory to explore the political phenomena of money that often occur in the community, and is supported by several theories and concepts supporting the theory of power, political participation and Political money. The research methods used in this study are qualitative. Research location in Sandik village, Batu Layar District, West Lombok. The informant in the study consisted of the community, the successful team of certain political candidates or contestants to other important figures within the village. Datacollection techniques are conducted by conducting field observations, in-depth interviews and documentation on interviews and photo activities. The results show that (1) the factorsthat cause political money in the community are the influence of the economic limitations of society, low quality of public education, and weak supervision conducted. (2) The process of political money is carried out directly by a certain political candidate or contestant and carried out indirectly through the intermediaries of others in providing and distributing thepolitics of the money. (3) The impact of the political practice of money can be detrimental to the democratic order and can cause other new problems in society to the Government, thus carrying a negative impact that is long term.